La forja de Isidro Gomá como adalid del antirrepublicanismo en la Iglesia de España (1927-1933) - Roberto Ceamanos Llorens (Cahiers de Civilisation Espagnole Contemporaine)
This article examines the work of Isidro Gomá y Tomás in the see of Tarazona and Tudela (1927-1933). Gomá, the archbishop of Toledo (1933-1940), is one of foremost personalities studied by Spanish Civil War historians, because of the backing he gave to the rebels. However, the period prior to his appointment as Primate of the Spanish Church is still unknown. This article shows how Gomá, during his time in Tarazona, led his diocese with a firm hand, and when the Republic came, took a hard line against the secular reforms, establishing himself as a key figure in the extreme antirepublican Catholic media. This led the Vatican to take him into consideration when it decided to cover the vacant see of Toledo.